2010
DOI: 10.1128/jvi.02365-09
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Correlates of Vaccine Efficacy after a Heterologous Simian Immunodeficiency Virus Challenge

Abstract: Determining the "correlates of protection" is one of the challenges in human immunodeficiency virus vaccine design. To date, T-cell-based AIDS vaccines have been evaluated with validated techniques that measure the number of CD8 ؉ T cells in the blood that secrete cytokines, mainly gamma interferon (IFN-␥), in response to synthetic peptides. Despite providing accurate and reproducible measurements of immunogenicity, these methods do not directly assess antiviral function and thus may not identify protective CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 64 publications
2
41
0
1
Order By: Relevance
“…Several studies indicate differences in the capability of virusspecific T cell clones to interfere with HIV-1 replication. Importantly, it has been demonstrated that an effective CTL response acting specifically against HIV-1 Gag, but not against other viral Ags, can be correlated with a significant reduction in viral load in HIV-1-infected patients (69)(70)(71) or in SIV-1-infected rhesus macaques (72). Therefore, HIV-1 Gag can be considered as an interesting model Ag.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate differences in the capability of virusspecific T cell clones to interfere with HIV-1 replication. Importantly, it has been demonstrated that an effective CTL response acting specifically against HIV-1 Gag, but not against other viral Ags, can be correlated with a significant reduction in viral load in HIV-1-infected patients (69)(70)(71) or in SIV-1-infected rhesus macaques (72). Therefore, HIV-1 Gag can be considered as an interesting model Ag.…”
Section: Discussionmentioning
confidence: 99%
“…To extend our findings that freshly sorted SIV-specific CD8 ϩ T cells cannot efficiently suppress viral replication in SIV-infected macrophages, we next tested bulk CD8 ϩ T cells in the viral suppression assay as previously described (17,28). We isolated bulk CD8 ϩ T cells from ECs and naïve animals using an anti-CD8 antibody that recognizes a conformational epitope of the CD8␣␤ heterodimer, thereby excluding natural killer cells, which express only CD8␣ (40,46).…”
Section: Bulk Cd8 ؉ T Cells That Suppress Viral Replication In Siv-inmentioning
confidence: 99%
“…Autologous cryopreserved PBMC were used to perform a virus inhibition assay essentially as previously described (43). Briefly, PBMC samples obtained before the study start and after the last vaccination were magnetically sorted into CD8-depleted PBMC (target cells) and positively selected CD8+ T cells (effector cells) using a non-human primate-specific CD8 Microbead kit (Miltenyi Biotec), according to the manufacturer's instructions.…”
Section: Virus Inhibition Assaymentioning
confidence: 99%